2020
DOI: 10.1007/s11136-020-02647-7
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of health-related quality of life among people with a physical disability and/or chronic disease during and after rehabilitation: a longitudinal cohort study

Abstract: Purpose To identify Health-related Quality of Life (HR-QoL) trajectories in a large heterogeneous cohort of people with a physical disability and/or chronic disease during and after rehabilitation and to determine which factors before discharge are associated with longitudinal trajectory membership. Methods A total of 1100 people with a physical disability and/or chronic disease were included from the longitudinal cohort study Rehabilitation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
2
8
2
Order By: Relevance
“…The large variation in the literature concerning clinically important change in PCS and MCS scores (32)(33)(34), means that it is challenging to determine whether the changes were clinically important. Nevertheless, the improvements in component scores from baseline to 1 year are in line with changes seen in a 1-year functional rehabilitation trajectory study conducted in Norway (15), and similar to reported improvements in the moderate outcome category in a Dutch 1-year follow-up study (16). The current study provides new knowledge that improvement achieved at 1 year after rehabilitation seems to persist over time.…”
Section: Change In Physical and Mental Functionsupporting
confidence: 88%
“…The large variation in the literature concerning clinically important change in PCS and MCS scores (32)(33)(34), means that it is challenging to determine whether the changes were clinically important. Nevertheless, the improvements in component scores from baseline to 1 year are in line with changes seen in a 1-year functional rehabilitation trajectory study conducted in Norway (15), and similar to reported improvements in the moderate outcome category in a Dutch 1-year follow-up study (16). The current study provides new knowledge that improvement achieved at 1 year after rehabilitation seems to persist over time.…”
Section: Change In Physical and Mental Functionsupporting
confidence: 88%
“…This implies that good quality of care leads to enhance quality of life of people with disability because quality of care is important factor in healthcare, disability services and rehabilitation. The results of this study confirms the previous empirical studies that quality of care influence significantly on quality of life of the people with disability (Zheng et al, 2014) because rehabilitation is an outcome of quality of care which directly improves quality of life of people (Seves et al, 2021). However, the result of this study is inconsistency with numerous previous empirical studies that quality of care has no significant effect on the quality of life of the people with disability (De Waele et al, 2005).…”
Section: Discussionsupporting
confidence: 69%
“…Empirical evidences from a study of QOL, perceived QOC and support, personal attitude towards disability among people with physical disability in China, showed that quality of care and support was playing a more important mediating role than PWPD's attitudes towards their own disability on the quality of life for people with disability (Zheng et al, 2014). Signifying that rehabilitation is an outcome of quality of care and more importantly improved quality of life was reported among people who received rehabilitation services compared to people with disabilities never received rehabilitation care (Seves et al, 2021). Quality of care is significant on quality of life of people with disabilities.…”
Section: Hypothesismentioning
confidence: 96%
“…Albeit exploratory, results related to the impact of attachment anxiety and attachment avoidance on CID-treatment outcomes set the stage for future research in this area. Examining predictors of outcome may help tailor treatment to better meet patient needs, and help identify individuals who may be at risk of poor treatment response and an unfavourable HRQoL trajectory (Seves et al, 2021).…”
Section: Discussionmentioning
confidence: 99%